Walking in Circles: Making Stories out of Landscapes - Linda Cracknell (Postscriptum Polonistyczne)
Using the example of her novel, Call of The Undertow, published in 2013, Linda Cracknell writes about how repeated walks in a new place rich with possibility resulted in a fictional narrative out of observation and sensation. She also draws on her non-fiction book, Doubling Back: Ten Paths Trodden in Memory, a book described as a combination of ‘memoir, travelogue and literary meditation’, inspired by re-treading former journeys on foot taken by herself or by others. Both books have involved a ‘multiple gaze’ across nature, social history, communities and inner lives, and share some creative methods. In both she’s attracted to liminal worlds, exploration and often to women who challenge boundaries. Motion is necessary to this writer’s imaginative writing, but in Doubling Back, the motion has itself become the subject. For the writer, the craft is similar but fiction feels a greater transformation of the material. For the reader, which kind of text provides a more visceral experience of having travelled herself, and is it necessary for the reader to be a walker in order to fully engage with accounts of journeys on foot?